2016
DOI: 10.1016/j.ajhg.2016.06.016
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis

Abstract: Circulating blood cell counts and indices are important indicators of hematopoietic function and a number of clinical parameters, such as blood oxygen-carrying capacity, inflammation, and hemostasis. By performing whole-exome sequence association analyses of hematologic quantitative traits in 15,459 community-dwelling individuals, followed by in silico replication in up to 52,024 independent samples, we identified two previously undescribed coding variants associated with lower platelet count: a common missens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…Instead, hyperexpression and knockdown experiments in human primary cells have shown that the long GFI1B is required for megakaryopoiesis, but not the short form (25), which may have an inhibitory effect on platelet production (26) (Figure 2). …”
Section: Gfi1 and Gfi1b Structure And Functionmentioning
confidence: 99%
“…Instead, hyperexpression and knockdown experiments in human primary cells have shown that the long GFI1B is required for megakaryopoiesis, but not the short form (25), which may have an inhibitory effect on platelet production (26) (Figure 2). …”
Section: Gfi1 and Gfi1b Structure And Functionmentioning
confidence: 99%
“…GFI1B is a hematopoietic transcription factor required for normal red blood cell and platelet production 34. In a companion paper, we demonstrate that the rs150813342 variant influences the relative amounts of two GFI1B transcript isoforms, a full-length (long) and short isoform lacking the alternatively spliced exon 5 22. We further demonstrate the lineage-specific role of the long GFI1B isoform on megakaryocyte development.…”
Section: Discussionmentioning
confidence: 61%
“…SHROOM3 rs10008637 associated with higher PCV is an LD proxy (r 2 =0.98) for rs13146355, a common intronic variant associated with lower serum creatinine in East Asians 20 and higher serum magnesium in Europeans 21. One of the PLT-associated loci, synonymous variant rs150813342 of GFI1B , is reported concurrently in an independent exome sequencing data set 22.…”
Section: Resultsmentioning
confidence: 95%
“…In erythrocytes, the conditional inactivation of Gfi1b leads to impaired differentiation of pro-erythroblasts to mature erythrocytes [31]. A long isoform of GFI1B that contains exon 5 is essential for megakaryopoiesis, while a short isoform lacking exon 5 is essential for its erythropoietic role [14]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a GFI1B mutation segregated with an isolated bleeding diathesis of variable severity in a family with mild to moderate macrothrombocytopenia and subtle red cell changes consisting of anisopoikylocytosis and increased red blood cell distribution width [10,11], and in a family with thrombocytopenia, enlarged hypogranular platelets and abnormally shaped red blood cells [12]. Indeed, GFI1B is known to participate in both megakaryopoiesis and erythropoiesis [13,14]. …”
Section: Introductionmentioning
confidence: 99%